The my-fun-with-words dictionary - Ertel, James, 1922-; Everds, John (Nashville : Southwestern Co., 1974)
A two volume picture dictionary with simple explanations of such familiar words to children as big, birthday, and intelligent and some slightly more difficult ones such as collide and similar.
Keywords: English language -- Dictionaries, Juvenile; Picture dictionaries, English -- Juvenile literature; English language -- Dictionaries; Picture dictionaries